(3GdJGQjN GdcHjQs - (3Ydj Hf GdMSf Hf gHI Gddg GdTGaYj GdOeTbj, CHh GdbGSe, KbI GdOjf, GHf YSGcQ , J (B571 (3g` s
(3ChdgG (B:s
(3CNHQfG GdMGaX CHh GdbGSe Ydi Hf GdMSf QMeg Gddg bGd CfHGfG CHh GdSYhO s
(3BNQgG (B:s
(3hcPdc jhdi Gddg HYV GdXGdejf HYVkG HeG cGfhG jcSHhf hdi OeTb SfI SJjf hKdKeGjI hGddg CYde HGdUhGH s
(3HgG fXGe GdJYbjHIs
(3LRA efg jHOC HJQLeI TOGO Hf ChS hjfJgi HJQLeI XGde Hf eQghH HgG HjGVs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B273s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdJGQjNs